Comparative effectiveness of topical lignocaine nebulization and airway nerve blocks for awake fiber-optic nasal intubation in TM joint ankylosis - Malla, Mohammad Sadiq; Farooq, Basharat; Najib, Rayees; Ashraf, Sameena (Asian Journal of Medical Sciences, 2021)
Background: Awake fiber-optic nasal intubation is a gold standard management of difficult airway in temporal mandibular (TM) joint ankylosis. Aims and Objectives: We compared topical lignocaine nebulization with airway nerve blocks for awake fiber-optic nasal intubation in TM joint ankylosis. Materials and Methods: Fifty patients of either gender were randomly allocated into two groups of 25 each. Group I received 10 ml of 2% lignocaine nebulization over a period for 20 min. Group II received bilateral superior laryngeal nerve block and transtracheal recurrent laryngeal nerve block (each with 2 ml of 2% lignocaine). Awake fiber-optic bronchoscopy-guided nasal intubation was done in all patients. All the patients received sedation during the procedure. The intubation time, intubating conditions, vocal cord position, cough severity, and degree of patient satisfaction were recorded. Student’s t-test was used to analyze parametric data, while the Mann–Whitney U-test was applied to non-parametric data and Fisher’s test to categorical data. P<0.05 was considered statistically significant. Results: The time taken for intubation was significantly shorter in Group II [110.2 (14.6) s compared with Group I (211.0 [22.3] s) (P=0.028 ss). The intubating conditions and degree of patient comfort were better in Group II compared with Group I. Although all patients were successfully intubated, patient satisfaction was higher in Group II. Conclusion: Airway nerve block is a better way of anesthetizing airway as compared to nebulization for awake fiber-optic nasal intubation. However, nebulization with lignocaine may be an alternative in situations where nerve blocks are not feasible or may be used as an adjuvant to nerve blocks.